Sustainable investment feasibility and optimization strategies for PLTSA Benowo: A system thinking approach - Putra, Iqbal Maulana Anggara; Sarasi, Vita (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the sustainability of investments and operational optimization strategies for the Benowo Waste-to-Energy Power Plant (PLTSa) in Surabaya using a System Thinking approach through Causal Loop Diagram (CLD) and Cost-Benefit Analysis (CBA). Data were obtained through a mixed-methods approach, combining semi-structured interviews with PT Sumber Organik, the Surabaya Environmental Agency, PT PLN, the National Energy Council, and academic experts in finance, health, waste management, and system thinking. Secondary data, including waste processing capacity, electricity output, tipping fee and electricity sales revenue, and operational costs, were collected from official reports, academic publications, Bappenas, the Ministry of Environment and Forestry, Surabaya Population Agency, and Kominfo Jatim, covering the period 2015–2023 with projections up to 2032. The CLD highlights dynamic interactions among waste quality, public participation, technological efficiency, policy support, and environmental impacts. Financial analysis indicates that PLTSa Benowo is economically feasible, with a Benefit-Cost Ratio (BCR) of 2.58 at design capacity and 1.81 at effective capacity, and a Return on Investment (ROI) of 157.55% and 81.47%, respectively. Sensitivity analysis shows that increases in operational costs and the removal of tipping fees reduce BCR and ROI values. Therefore, cost efficiency, technology upgrading, revenue diversification, and sustainable policy support are needed to maintain the long-term viability of waste-to-energy projects in developing countries.